Surgical Resection or Ablation for Recurrent Pancreatic Ductal Adenocarcinoma: An Analysis of Oncologic Outcomes According to the Recurrence Type. Issue 3 (9th September 2021) - Lee, Boram; Han, Ho-Seong; Lee, Jun Suh; Yoon, Yoo-Seok
Abstract : Objective: To evaluate the survival benefits of curative-intent treatment (CIT, including surgery or ablation) for recurrent pancreatic ductal adenocarcinoma (PDAC) depending on the recurrence type and compared the survival outcomes with other treatment modalities. Background: The treatment for recurrent PDAC is mostly chemotherapy or best supportive care (BSC). Still, the role of CIT for recurrent PDAC is not well established. Methods: PDAC patients who underwent pancreatectomy between 2004 and 2019 were included. Recurrences were categorized as locoregional (LR), distant, or disseminated. Recurrent PDAC management was classified as CIT, chemotherapy ± radiation therapy (CTX ± RTX), or BSC. The survival after recurrence (SAR) rate was measured from the first day of recurrence to the date of death or last follow-up. Results: Two hundred eighteen patients had recurrent PDAC and were analyzed (27 CIT, 128 CTX ± RTX, 63 BSC). The 1-, 3-, and 5-year SAR rates were 65.4%, 11.5%, and 11.5% for CIT, 42.1%, 4.0%, and 0% for CTX ± RTX, and 15.9%, 1.6%, and 0% for BSC, respectively. Subgroup analysis indicated the SAR rate was significantly better in the CIT group than in the CTX ± RTX and BSC groups in LR type ( P = 0.027) and distant type ( P < 0.001). In multivariate analysis, the albumin level at recurrence (hazard ratio, 2.14; 95% confidence interval, 1.15–18.3, P = 0.038) and operation time of the second operation (hazard ratio, 0.98; 95% confidence interval, 0.97–0.99, P = 0.021) were associated with a favorable prognosis of SAR in the CIT group. Conclusions: CIT should be considered in recurrent PDAC for LR and distant metastases in selected patients. Abstract : Mini-Abstract: Pancreatic ductal adenocarcinoma (PDAC) recurrence is common despite curative resection. We evaluated the survival benefits of curative-intent treatment (CIT) for recurrent PDAC depending on the recurrence type and compared survival outcomes with other modalities. CIT is a possible treatment for locoregional and distant recurrence of PDAC in selected patients. Supplemental Digital Content is available in the text.